Cross-Cultural Mental State Reading Ability in Antillean Dutch, Moroccan Dutch, and Dutch Young Adults. (April 2019) - van der Meulen, Anna; de Ruyter, Doret; Blokland, Arjan; Krabbendam, Lydia
Understanding how bicultural and monocultural individuals are oriented toward the cultures they come into frequent contact with can increase insights into their adaptation and well-being. Previous research has shown a relation between culture and mental state reading in the form of the cultural in-group effect, which is defined as the advantage in reading mental states from the own cultural group compared with other groups. Thus, orientation toward cultures can be assessed not only in self-reported behavioral and psychological acculturation but also in the domain of social–cognitive abilities. The aim of the current research is to gain insight into acculturation in the social–cognitive ability of mental state reading. In addition, it explores how this facet of acculturation is related to the more traditionally studied behavioral and psychological acculturation. Cross-cultural mental state reading, language and possession of friends (behavioral acculturation), and cultural identification (psychological acculturation) were assessed in Antillean Dutch ( n = 128), Moroccan Dutch ( n = 204), and Dutch ( n = 349) young adults between 19 and 24 years old ( M = 21.57 years, SD = 1.38 years). For cross-cultural mental state reading, the in-group effect was confirmed for the Dutch but not for the Antillean Dutch and Moroccan Dutch participants. Furthermore, there were no consistent associations between mental state reading and behavioral and psychological acculturation in the three groups. The present results extend fundamental research on cross-cultural mental state reading and also help to further understand the orientation of these specific cultural groups.